Long-term clinical course and outcomes of patients with microscopic polyangiitis-associated interstitial lung disease - Kim, Min Jee; Lee, Donghee; Choe, Jooae; Song, Jin Woo (Frontiers in Pharmacology, 2023)
Background: Interstitial lung disease (ILD) is a significant complication associated with microscopic polyangiitis (MPA) that has a poor prognosis. However, the long-term clinical course, outcomes, and prognostic factors of MPA-ILD are not well defined. Hence, this study aimed to investigate the long-term clinical course, outcomes, and prognostic factors in patients with MPA-ILD. Methods: Clinical data of 39 patients with MPA-ILD (biopsy proven cases, n = 6) were retrospectively analyzed. High resolution computed tomography (HRCT) patterns were assessed based on the 2018 idiopathic pulmonary fibrosis diagnostic criteria. Acute exacerbation (AE) was defined as the worsening of dyspnea within 30 days, with new bilateral lung infiltration that is not fully explained by heart failure or fluid overload and that does not have identified extra-parenchymal causes (pneumothorax, pleural effusion, or pulmonary embolism). Results: The median follow-up period was 72.0 months (interquartile range: 44–117 months). The mean age of the patients was 62.7 years and 59.0% were male. Usual interstitial pneumonia (UIP) and probable UIP patterns on HRCT were identified in 61.5% and 17.9% of the patients, respectively. During the follow-up, 50% of patients died, and the 5- and 10-year overall survival rates were 74% and 42%, respectively. AE occurred in 18% of the patients. The non-survivors had higher neutrophil counts in bronchoalveolar lavage (BAL) fluid and more frequent AE than the survivors. In the multivariable Cox analysis, older age (hazard ratio [HR], 1.07; 95% confidence interval [CI], 1.01–1.14; p = 0.028) and higher BAL neutrophil counts ([HR], 1.09; [CI], 1.01–1.17; p = 0.015) were found to be the independent prognostic factors associated with mortality in patients with MPA-ILD. Conclusions: During the 6 years-follow-up, 50% of patients with MPA-ILD died and approximately 20% experienced AE. Our results suggest that older age and higher BAL neutrophil counts mean poor prognosis in patients with MPA-ILD.